2021
DOI: 10.1038/s41388-021-01963-7
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein IQGAP1 links heat-induced stress signals to alternative splicing regulation in gastric cancer cells

Abstract: In response to oncogenic signals, Alternative Splicing (AS) regulators such as SR and hnRNP proteins show altered expression levels, subnuclear distribution and/or posttranslational modification status, but the link between signals and these changes remains unknown. Here, we report that a cytosolic scaffold protein, IQGAP1, performs this task in response to heat-induced signals. We show that in gastric cancer cells, a nuclear pool of IQGAP1 acts as a tethering module for a group of spliceosome components, incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 74 publications
(80 reference statements)
0
25
0
Order By: Relevance
“…One specific example of the interactions between IQGAP1 and splicing proteins is a study by Birladeanu et al that links hnRNPs, another large family of splicing factors, to IQGAP1 in the context of gastric cancer . Their study showed that IQGAP1 regulates alternative splicing through hnRNPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One specific example of the interactions between IQGAP1 and splicing proteins is a study by Birladeanu et al that links hnRNPs, another large family of splicing factors, to IQGAP1 in the context of gastric cancer . Their study showed that IQGAP1 regulates alternative splicing through hnRNPs.…”
Section: Resultsmentioning
confidence: 99%
“…One specific example of the interactions between IQGAP1 and splicing proteins is a study by Birladeanu et al that links hnRNPs, another large family of splicing factors, to IQGAP1 in the context of gastric cancer. 94 Their study showed that IQGAP1 regulates alternative splicing through hnRNPs. In a gastric cancer cell line, they found that IQGAP1 can interact with spliceosome component proteins, including hnRNPs and SR proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared NUGC4 and NUGC4-IQGAP1 KO cells in a wound healing assay and found more than 50% reduction in the migration rate of the KO cells compared to the parental ones (Figure 4F, S4F). Of note, IQGAP1 depletion did not impair migration of MKN45 cells (Birladeanu et al 2021), in which NDUFS4 AS and expression were also unaffected (Figure S2D-F). Overall, our data point towards a direct effect of IQGAP1 on the mitochondrial respiratory chain, at least partially through the regulation of AS of NDUFS4, the deregulation of which can be linked to other mitochondrial defects (mitochondrial fragmentation/aggregation, reduction of mitochondrial ROS production) observed in the KO cells.…”
Section: Mitochondrial Physiology Is Affected In Gastric Cancer Cells...mentioning
confidence: 91%
“…Given that nuclear IQGAP1 is differently distributed in the nuclei of gastric cancer cells of different origin 11 , we studied further the consecutive different AS regulation by IQGAP1. We present herein conclusive evidence on the participation of IQGAP1 in the oxidative metabolism of gastric cancer cells via its involvement in the regulation of AS of components of the mitochondrial electron transport chain.…”
Section: Introductionmentioning
confidence: 99%